NUTRITIONAL STATUS AND SOME RELATED FACTORS IN CHILDREN UNDER 24 MONTHS AT THE GENERAL CLINIC OF HOA BINH PROVINCIAL CENTER FOR DISEASES CONTROL 2023-2024 - To, Thi Quyen (Tạp chí Sinh lý học Việt Nam, 2024)
Introduction: During the first two years of life, children have a high demand for essential nutrients that support physical growth and the gradual maturation of organ systems. Hoa Binh is a mountainous province in the Northwest region of Vietnam, characterized by complex terrain and difficult transportation. Objectives: 1. To assess the nutritional status of children under 24 months at the General Clinic of the Center for Disease Control, Hoa Binh Province, in 2023-2024. 2.To describe some factors related to the nutritional status of children under 24 months at the General Clinic of the Center for Disease Control, Hoa Binh Province, in 2023-2024. Methods: Cross-sectional descriptive study on Children under 24 months of age who visit the clinic or vaccination center in the study area and their moms. Results: The prevalence of underweight, stuning and wasting were 16.1, 13.8 and 8.7%, respectively. Birth weight less than 2500 grams, children older than 6 months old, not vaccinated enough for their age, and not breastfed have a statistically significant higher rate of underweight malnutrition. Maternal age over 35 and no breastfeeding early after birth have a statistically significant higher rate of stunting. Families with more than two children, those who are not fully vaccinated according to age, and those who do not breastfeed are groups with a significantly higher rate of wasting. Conclusion: The prevalence of malnutrition of study subjects was still high, some related factors of each type were showed. May be there is an urgent need to implement good interventions to improve children health.